Mechanical Properties of Fiber-Reinforced Concrete Using Composite Binders - Roman Fediuk; Aleksey Smoliakov; Aleksandr Muraviov (Advances in Materials Science and Engineering)
This paper investigates the creation of high-density impermeable concrete. The effect of the “cement, fly ash, and limestone” composite binders obtained by joint grinding with superplasticizer in the varioplanetary mill on the process of structure formation was studied. Compaction of structure on micro- and nanoscale levels was characterized by different techniques: X-ray diffraction, DTA-TGA, and electron microscopy. Results showed that the grinding of active mineral supplements allows crystallization centers to be created by ash particles as a result of the binding of Ca(OH)2 during hardening alite, which intensifies the clinker minerals hydration process; the presence of fine grains limestone also leads to the hydrocarboaluminates calcium formation. The relation between cement stone neoplasms composition as well as fibrous concrete porosity and permeability of composite at nanoscale level for use of composite binders with polydispersed mineral supplements was revealed. The results are of potential importance in developing the wide range of fine-grained fiber-reinforced concrete with a compressive strength more than 100 MPa, with low permeability under actual operating conditions.